Enemy at the gates - Copyright Collection (Library of Congress) (c 2001. Paramount, 2001)
Like Saving Private Ryan, Enemy at the Gates opens with a pivotal event of World War II--the German invasion of Stalingrad--re-created in epic scale, as ill-trained Russian soldiers face German attack or punitive execution if they flee from the enemy's advance. Director Jean-Jacques Annaud captures this madness with urgent authenticity, creating a massive context for a more intimate battle waged amid the city's ruins. Embellished from its basis in fact, the story shifts to an intense cat-and-mouse game between a Russian shepherd raised to iconic fame and a German marksman whose skill is unmatched in its lethal precision. Vassily Zaitzev (Jude Law) has been sniping Nazis one bullet at a time, while the German Major Konig (Ed Harris) has been assigned to kill Vassily and spare Hitler from further embarrassment.
Copyright: MP Film Management Dos Prod. GmbH & Company, KG, Swanford Films, Ltd., Little Bird, Ltd. Appl. au.: Mandalay Pictures, LLD, employer for hire. Prev. reg.: Some music prev. reg. NM: all other cinematographic material. DCR 2001; PUB 16Mar01; REG 3Jul01; PA1-039-867.
Sources used: copyright data base; copyright data sheet.
Directors: Jean-Jacques Annaud Writers: Jean-Jacques Annaud, Alain Godard Producers: Jean-Jacques Annaud, Alain Godard, Alisa Tager, John D. Schofield, Jörg Reichl
Jude Law, Ed Harris, Joseph Fiennes, Rachel Weisz, Bob Hoskins
Keywords: Nazis -- 1942. -- Fiction; Feature